Penciptaan Lingkungan Edukatif dalam Pembentukan Karakter: Studi terhadap Aplikasi Pemikiran Ibnu Jama’ah - Hery Noer Aly (Universitas Darussalam Gontor, 2012)
This study is a rediscovery enterprise on educational thought of Ibn Jama’ah in his famous book, al-Tadhkirah. It is basically the book on learning and teaching. But, much more than a book on technic and strategy , it is full of moral message which conducts whole process of learning and teaching, and in turn creates an educating environment. The significance of this study due to moral decadence among the nation. Corruption, for instance, is not only available among the leaders and bureaucrates, but also among the peoples. Delinquency is not only the habit of young generation, but now suffered by parents who can not give a good sample. That moral decadence is not deal with the poverty of moral conduct; there are treasury and haritage of it, either from religous or traditional resource. But that old values available in many documents are not internalized yet, in additon to the fast-coming of foreign culture which is not in accord with Indonesian culture. Here we see that the issue is not the content of value education, but the strategy developed in the process. So that, al-Tadhkirah will be studied with content analysis approach to find out the possibility of application of his thought in moral education. The study finally discovered that the thought of Ibn Jama’ah is very possible to be applied. The only precondition is the commitment of all stakeholders to create educating environtment based on regulation formulated by themselves.